عــوامل تفشي الظواهــر اللاأخلاقية بالوسط الجامعي الجزائري - هدار, مصطفى سليم (دفـاتر المـــــــــــخبـر; No 19 (2018): مجلة دفاتر, 2018)
يهدف المقال الحالي إلى إلقاء الضوء على بعض أهم العوامل المؤثرة بطريقة أو بأخرى في تفشي الظواهر اللاأخلاقية بالوسط الجامعي الجزائري، التي تنتشر بشكل غير مسبوق في الآونة الأخيرة رغم دور الجامعة في توجيه السلوك الأخلاقي للأفراد. صحيح أن " الأخلاق " كمجال للبحث كثير الاستعمال في حقول البحث بالعلوم التربوية، لكنه يدفع لتساؤلات جمة لا تتمحور فقط حول طبيعته أو ماهيته بين الشق الإيجابي والشق السلبي، بل حول الآليات والوسائل الإمبريقية أو الإحصائية المستعملة لقياس وفهم هذا المصطلح. وسنحاول في هذا السياق أن نعطي لمحة وجيزة عن بعض العوامل والمفاهيم التي تلعب دورا مهما في نشأة وتطور الظواهر اللاأخلاقية وبالتالي في تفشيها بالوسط الجامعي الجزائري. The purpose of the present article is to shed light on the factors that affect in one way or another the propagation of immoral phenomena in Algerian academic circles, because these phenomena spread in an incredible way recently despite the fact that the university participates in the orientation of moral acts in individuals. It is true that "morality" as a field of research is one of the most commonly used concepts in the field of education studies, but it raises many questions not only about its nature and its definition between Positive and negative, but also on the tools and ways of measuring empirical or statistical use to understand this concept.  We will try in this regard to give a brief overview on some factors that play an important role in the creation and development of immoral phenomena in Algerian academic circles.